Pola Komunikasi Guru Dalam Menghadapi Siswa Berkebutuhan Khusus Tundaksa Di Sekolah Luar Biasa Negeri Serdang Bedagai - Dian Paramita; Muhammad Husni Ritonga (JURNAL ILMIAH EDUNOMIKA, 2023)
Special needs children themselves are usually abbreviated as ABK, which is a condition of child limitations that occur from birth or due to illness. This research uses qualitative research methods with a descriptive case study approach, which describes a specific, limited, in-depth case using a variety of sources, such as interviews, observations, documents. This research aims to find out the communication patterns carried out by teachers in dealing with children with disabilities. Children with special needs (ABK) have the same rights as other normal children in all aspects of life. disability itself is a disease with nerve disorders that inhibit the motor system. It is a congenital disease or can also be caused by an accident. In carrying out teaching and learning activities, it is certainly not the same as teaching normal children. Teachers and parents are important supporters in guiding children with disabilities, especially in the world of education, not only teachers at school, parents at home can also be teachers for their children. Teachers should master competencies when educating these children. In addition, patience must also be instilled so that during the teaching and learning process the student can be calm and easy to understand.